Experimental behaviour of steel beam-column subassemblies with different slab configurations. (November 2019) - Chaudhari, Tushar; MacRae, Gregory; Bull, Des; Clifton, Charles; Hicks, Stephen
Abstract: Four full-scale steel moment resisting frame (MRF) beam-column subassemblies with different slab configurations, plus another without a slab, were experimentally tested under reversed cyclic loading to drifts of up to 5%, to determine their strengths and deformation capacities. The slabs consisted of concrete, with different arrangements of reinforcing bars, cast on cold-formed steel decking. They were connected to structural steel beams using shear studs. The different slab configurations included: (i) full isolation of the slab from the column, end plates, bolts and haunches; (ii) a shear key within the column web with the slab isolated from the column flange outside faces; (iii) a modified shear key within the column web with a confinement plates and slab isolated from the outside faces of the column flanges; and (iv) a full depth confined slab around the columns. It was shown that slab damage could be avoided by fully isolating the column from the slab with appropriate material. The isolated slab subassembly lateral strength was that of the bare frame with enhanced ductility. In the other tests without a fully confined slab, the strength increased up to 30% but degraded to that of the bare steel subassembly alone as a result of slab damage. Slab failure modes included concrete spalling where the slab was bearing against the column, shear failure of the concrete shear key between the flange tips and failure within the shear key due to slab reinforcing bars slicing through the concrete there. By using a confined full depth slab, the strength and stiffness increased by almost 50 and 87%, respectively and there was little strength loss. Highlights: Four beam-column subassemblies of an internal joint of an MRF with different slab detailing were tested experimentally. The slab subassembly strength was increased but then degraded to that of a bare steel frame. Slab isolation from column resulted in a similar strength, but greater deformation capacity, than the bare steel frame. By detailing carefully in such a way that the slab is confined, there was no significant strength degradation. The strength due to the slab was increased by 50%, which is important for capacity design of the column, and panel zone. Methods to detail the slab for different levels of performance are clearly described and design guidance is provided.